Connected yet Isolated: Digital Social Disruption and Its Impact on Learning and Interaction in Rural Elementary Education - Lia Fherdiana; Sriyanto Sriyanto; Subuh Anggoro; Anang Widhi Nirwansyah; Văn Kim Hoàng Hà (Jurnal Pendidikan Progresif, 2026)
Recent technology and gadget use have profoundly affected children and how they communicate and learn, including those living in remote areas. The goal of this study is to understand the emerging social phenomenon of digital social disruption and its ramifications for social communication and academic engagement, with a focus on elementary school children in rural areas and on intensive technology use. The study's rural context is digital social disruption and its impact on children's social engagement and learning. The study employs a qualitative approach and a case study design. Data were obtained through community and classroom observations, semi-structured interviews with parents, students, and teachers, and relevant documents collected from school and home. When relating the discovered themes to the three forms of digital social disruption, it was identified that the first digital social disruption involves the transition from a participatory social engagement to a digital individualised participation where social empathetic engagement and social/interpersonal skills are noticeably diminished; the second involves a prevalent digital distraction and poor collective learning culture that causes a focus deficiency on academic achievement tasks; and lastly, the school and family collaboration in fostering children's digital capacities has been poor resulting in inadequate digital supervision. Rural youth social ecosystems are being impacted by digital individualization through the dismantling of established social collectives. The study recommends that more responsive digital literacy programs and school-family collaboration on the responsible use of technology, and revitalizing children’s social engagement are important. Keywords: social disruption, digital era, social interaction, learning concentration